An Avifaunal Survey in Selected Sites Along Bago River, Negros Occidental, Philippines - Bacosa, Rogie; Bangoy, Shirley; Averia , Leonardo T.; Bucol, Abner A.; Menes, Carmen C; Linaugo, Joji D.; Dales, Alma (Silliman Journal, 2022)
The avifaunal species occurring in forest fragments and in a coastal marsh associated with the Bago River were surveyed from July to September 2009 and from February to April 2010. Using deliberate search, mist netting and transect walk, 129 species of birds belonging to 42 families were recorded, of which 15 are Philippine endemics, 68 are resident species, and 46 are migrants. Two threatened species were recorded during the study while three bird species were recorded as additions to the avifauna of Negros. Conservation of the remaining habitats for birds along the Bago River should be immediately implemented.